New NP job search experience: Opportunities and obstacles. Issue 12 (December 2020) - Horvath, Emily; Higgins, Karen
Abstract : Abstract: This descriptive study investigated new NPs' job search experience including the job search process, employment negotiation, and compensation. The majority of new graduates found a job through networking within 3 months in a specialty practice or family medicine. Lack of experience and few available positions were employment obstacles. Abstract : This descriptive study investigated new NPs' job search experience including the job search process, employment negotiation, and compensation. The majority of new graduates found a job through networking within 3 months in a specialty practice or family medicine. Lack of experience and few available positions were employment obstacles.